Video Profil BUMDes Sebagai Media Promosi Desa Surabaya Timur - Mardian Herri Pratama; Desy Misnawati; Isna Wijayani (MUKASI: Jurnal Ilmu Komunikasi, 2022)
With the Republic of Indonesia Law no. 6 of 2014 concerning Villages creates a hope for village sustainability regarding the distribution of Village Funds, revitalization of village development, implementation of village government, to the utilization of the potential and local wisdom of the village itself. However, in Indonesia, the implementation of BUMDes has not been fully implemented. Moreover, in its implementation in some areas, the existence of BUMDes is still unable to run efficiently and is able to contribute to the development and empowerment of residents in the village. This research intends to find out the potential and make Video Profiling BUMDes as a promotional media for East Surabaya Village, Banding Agung District, Ogan Komering Ulu Selatan Regency, South Sumatra Province, which is a village whose BUMDes has a geographical location right above Lake Ranau. Other objectives of this research are: first, to find out the form of participation of the village government and residents in managing and utilizing BUMDes. Second, to find out the contribution of BUMDes in helping the economy and the welfare of the community. Third, to assist in promoting BUMDes and the potentials around them in the form of BUMDes Profiling Videos.